ANALISIS KEMAMPUAN GURU DALAM MEMPERSIAPKAN PEMBELAJARAN MATEMATIKA MENGGUNAKAN MULTIMEDIA INTERAKTIF - Masnia, Fakhriatul; Maimunah, Maimunah; Roza, Yenita (STKIP Andi Matappa, 2021)
Mathematics is a means of scientific thinking to lead to the development of science and technology that is very important and useful in everyday life so that mathematics is studied at every level of education from elementary school to college. Efforts are made to improve education in Indonesia by making changes in learning one of them with interactive multimedia. By making changes in teacher learning can be the more efficient time in learning so that it does not run out just to be repeatedly written and teachers are helped by the presence of interactive multimedia. The research was conducted at 4 state junior high schools/ MTs, Dumai in October 2020. The purpose of the research is to find out the ability of teachers in creating interactive multimedia. The data analysis used refers to the analysis of quantitative data obtained from questionnaires with 14 respondents. The subject of the study was a math teacher in the 4 schools. The sample in this study was 14 teachers using purposive sampling techniques. Based on research obtained from the results of the questionnaire, there were two teachers who had the highest score of 76.66% and the lowest score of 50% was also obtained by two teachers. The average teacher in four schools after getting training guidance can already be in the creation of interactive multimedia using the Microsoft PowerPoint application.